ANALISIS STRATEGI PUBLIC RELATIONS PT. BANK BCA SYARIAH KCP BEKASI DALAM MEMPROMOSIKAN PRODUK PEMBIAYAAN KPR IB - Amalia, Rizky; Isnandar, Fajri Rian (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2023)
A public relations strategy is needed to support effort to promote and market a product. Competition among sharia-based banks is also getting tighter and allowa people to freely choose which products and bank are their short or long term needs. The general public still needs information and explanations regarding aspects of sharia-based financial intitutions, especially product facilities that can be utilitized by prospective customers. Therefore it is necessary to have a public relations strategy for PT. Bank BCA Syariah in promoting KPR iB financing products.In this study using a qualitative approach. The method used is descriptive analysis, data collection techniques through observation techniques, inteviews.The strategy carried out by the Public Relations Strategy of PT. Bank BCA Syariah KCP Bekasi in Promoting iB Mortgage Financing Products, the use of the media is an important part of promoting iB Mortgage Financing Products. The types of media used are online media, print media, offline media and in person. PT. Bank BCA Syariah KCP Bekasi in promoting financing products is considered effevtive by carrying out thus strategy which has an impact on increasing the recognition of these products by the public.